Equações monoespecíficas de incremento em área basal de Handroanthus serratifolius (Vahl) S.O.Grose (ipê amarelo) e Handroanthus impetiginosus (Mart. ex DC.) Mattos (ipê roxo) da floresta tropical pluvial do Acre - Gama, Lorenna Eleamen da Silva (2017)
In natural forests rarely considers the forest structure and the growth rate of the species as criteria for management, which is based on species groups with distinct characteristics. Given this assumption, this work was developed seeking to advance in the knowledge of the rate of growth of timber species exploited in the East of the State of Acre in order to contribute to the sustainable exploitation of these forests. For this was modeled the growth of Handroanthus impetiginosus (Mart. Ex DC.) Mattos (ipê roxo) and Handroanthus serratifolius (Vahl) S. O. Grose (ipê amarelo) with measured data with the technique of growth ring analysis. In the regression model were investigated covariates associated with size and morphology of crown, competitive status, sanity and the load of lianas in the crown, as descriptors of the basal area increment rate. The study was carried out with Amazon rainforest trees, measured in the municipality of Porto Acre, Acre state, in particular area under sustainable forest management adopted by IMAC – Institute of environment of Acre. With the Pressler borer were collected, the height of the dbh, four rolls of increment of 0.5 mm in diameter and approximately 10 cm in length, obeying the cardinal points. The rolls were extracted from trees H. impetiginosus sample (n = 30) and H. serratifolius (n = 35) in a diametric amplitude between 13.5 cm to 88.1 cm dbh, totaling 260 rolls of increment. The width of the growth rings was measured on the rays towards bark/pith, in each roll with increment of tablet, with magnifying glass attached and TSAP-WinTM Scientific software. The width of the growth rings were rebuilt the dimensions of the dbh and the increment rates corresponding to the period from 2011 to 2014. The regression model was adjusted for Ordinary Least Squares considering hypothetical normal distribution, Generalized Linear Models considering distribution Gamma and logarithmic link function. The selection of the covariates considered the correlation with periodic basal area growth. The selected model had selected variables the diameter (dbh), height (h), h/d ratio and Hegyi competition index. The presence of multicollinearity between the covariates was corrected by Ridge Regression procedure. Based on statistical criteria and residual evaluation, adjusted growth model with the addition of the constant K = 0,024 to the coefficients of the model proved to be suitable to describe the variation of periodic annual increment in basal area (IPAg).